(untitled) (Development Service Industry Management, 2025)
Ukrainian economy is in a state of high instability due to military aggression, which slows down the development of SMEs. Management is looking for effective marketing tools to maintain competitiveness, expand markets and attract customers. The implementation of targeted advertising on social media is becoming increasingly important. Online advertising, especially on social media, is very popular. In Ukraine, over 29 million internet users, about 50% of whom are social media users. This creates significant potential for the development of Ukrainian SMEs through targeted advertising. Targeted Meta Ads (Facebook, Instagram, Messenger, Audience Network) is an effective tool that provides automation, personalisation and reporting, allowing for the most efficient use of the advertising budget. However, SMEs face disadvantages of Meta Ads: high requirements for targeting specialists, high content competition, Meta policy restrictions, use of personal data. Identifying and overcoming these shortcomings will increase the effectiveness of marketing communications. The purpose of the study is to theoretically and practically substantiate the effectiveness of marketing tools for the development of SMEs in unstable conditions. Analysis of social media popularity in Ukraine shows that Facebook and Instagram have the greatest potential for targeted advertising due to the versatility of Meta Ads. AI-powered tools like Advantage+ Campaigns, Advantage+ Shopping Campaigns, and Custom Audiences automate advertising. However, the complexity of settings, competition, and ethical aspects of data use require practical recommendations: campaign goal selection, automatic budget allocation, use of Lookalike and Advantage+, creative adaptation, regular analytics, compliance with Meta policy, monitoring updates, engaging experts. The study confirmed that Meta Ads is one of the most effective targeted advertising tools for SMEs in Ukraine. Unique platform features such as Advantage+ Campaigns, Audience Network, and integration with the Meta ecosystem ensure automation, personalisation, high targeting accuracy, and ROI. Key advantages of Meta Ads identified: flexibility in ad placement, a wide range of formats, AI-powered automation, detailed analytics. Custom and Lookalike Audiences effectively expand reach and tailor campaigns to business needs. Drawbacks limiting Meta Ads use: strict content policy, high competition, complexity of setup and optimisation, ethical challenges of personal data use. Prospects for further research: developing recommendations for adapting Meta Ads to the Ukrainian market, studying the effectiveness of new features (Advantage+ Shopping Campaigns) across industries. Successful implementation of recommendations will improve advertising campaign effectiveness and SME competitiveness in Ukraine.